Niosomes entrapment capacity of ketoprofen and prediction transdermal administration - rahman, Latifah; Ismail, Isriany; Wahyudin, Elly (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Niosomes are vesicles system that have applications in the delivery of lipophilic,hydrophilic and amphiphilic drugs. Ketoprofen, is very insoluble in water and cause gastric irritation when taken orally. It is very important to develop a transdermal delivery system for ketoprofen. This research was aimed to design niosomes which can deliver ketoprofen via transdermal route. Experiments were designed to incorporate ketoprofen into niosomes with lipid film hydration method. Lipid mixture consist of cholesterol and sorbitan ester (span 20, 60, 80). Niosomes which can deliver ketoprofen trough the skin barrier determined by calculating amount of ketoprofen in the blood of rabbit. The type of sorbitan ester was chosen based on the highest drugs entrapment and ketoprofen as drugs model. Preparation of niosomes was optimized for the highest percent drug entrapment by increasing molar concentration of lipidmixture with the stable comparison of 1:1. This research result are niosomes with lipid mixture span 60 and cholesterol have the highest drug entrapment efficiency of niosomes 66.16% with range size 1–6 µm. Niosomes can deliver ketoprofen to the systemic circulation via transdermal route with plasma level concentration achieved in 1.5 hour.Key words: niosomes, ketoprofen, transdermal